Application of the Cantol Roudhoh Method to Improve Student's Reading Ability in RA Siti Fatimah - Fahmi, Muhammad (Devotion : Journal of Research and Community Service, 2021)
The application of learning to read cantol roudhoh is one of the learning techniques that can improve children's language skills. This technique is very suitable for early childhood learning. The results of research conducted at RA Siti Fatimah, Harjamukti Village, Cirebon City, showed that the objective conditions of language learning were studied from the teacher's perspective, positive responses of children, teaching and learning processes, and supporting facilities, using the cantol roudhoh method which was applied in developing aspects of language, and skills children's language that can develop as expected. The implementation of this raudhoh hook method in its application process at RA Siti Fatimah is to practice in class A, which is to introduce hooks from her friends in clothes to her friends, Zahra, after reaching the target of her friends, Zahra continues on package B, which is entering the introduction of vocal groups (a, i, u, e, o), after that they enter the ng (cat) group, then enter the Koran group (nga, ngi, ngu, nge, ngo) and mosquitoes (nya, nyi, nyu, nye, nyo ). The last stage is the introduction of hooks with consonants.